2020
DOI: 10.1108/ejim-05-2020-0166
|View full text |Cite
|
Sign up to set email alerts
|

Technological innovation research in the last six decades: a bibliometric analysis

Abstract: PurposeThis study aims to explore the evolutionary trajectories of technological innovation using 1,361 documents to determine the most cited documents, influential authors, prominent journals and leading countries in the field of technological innovation research.Design/methodology/approachIn this paper, the intellectual structure of technological innovation literature was studied using bibliometric co-occurrence and co-citation analyses. The authors focused on the 1,361 documents in this research stream publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 95 publications
0
26
0
Order By: Relevance
“…First, by employing a BA, it contributes systematic insights into the evolution of neuroscience in EL and management field. This is the first study to propose a literature review that combines neuroscience and management literature using specific BA techniques recognized in several management disciplines (Akbari et al , 2020b; Suominen et al , 2019). Mapping the literature allows key research areas in the field to be identified, as well as the authors working in the field.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, by employing a BA, it contributes systematic insights into the evolution of neuroscience in EL and management field. This is the first study to propose a literature review that combines neuroscience and management literature using specific BA techniques recognized in several management disciplines (Akbari et al , 2020b; Suominen et al , 2019). Mapping the literature allows key research areas in the field to be identified, as well as the authors working in the field.…”
Section: Discussionmentioning
confidence: 99%
“…Innovation management is driven by the realization that innovation is a key factor in the competitiveness and survival of an organization (Akbari et al , 2020b; Ort and van der Duin, 2008). Indeed, it is an organizational activity relates to changes, where managers establish new processes and new activities, while leaders define new directions and motivate people (Hamel, 2006; Kotter, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical framework and study hypotheses Technological opportunism and innovation performance Numerous scholars have cited various sources for the adoption of innovations (see Akbari et al, 2020), which include the use of internal resources (knowledge-based and R&D), external resources (external suppliers) and the use of internal and external resources to drive innovation. Others (Cohen and Levinthal, 1990;Teece et al, 2006;Zahra and George, 2002) established that absorption capacity, dynamic capabilities and complementary assets as sources of innovation.…”
Section: Entrepreneurial Orientation On Technological Opportunismmentioning
confidence: 99%
“…Success in technology innovation depends on the firm's capabilities, organizational innovation (Le Bas et al , 2015), learning, resource allocation, organization and strategic planning (Guan et al , 2006). Notwithstanding the abundant research on technology innovation, scholars recognize that research and development (R&D) are not enough for technical innovation and development but rather it is necessary to develop tools to increase investment in new and emerging technologies as core factors in firm and economic growth (Akbari et al , 2020; De Visser et al , 2010). In this regard, the relevance of the complementary nature of entrepreneurship and innovation is acknowledged, since a combination of the two is vital to firm performance as technology innovation has to address market needs and requires entrepreneurship if it is to realize commercial success (Dess et al , 1999; Urban and Wood, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Companies and policymakers need to actively respond to global challenges and provide digital innovative solutions to accelerate the transformation towards a more circular and green economy, creating new jobs and sustainable growth (Akbari et al , 2021; Agostino and Costantini, 2021; Almunawar et al , 2022a, 2022b; Jirakraisiri et al , 2021; Tu and Wu, 2020; Vaska et al , 2021; Zhang et al , 2021).…”
Section: Introductionmentioning
confidence: 99%